Multilingual education and sustainable diversity work : from periphery to center - Skutnabb-Kangas, Tove.; Heugh, Kathleen (New York : Routledge, 2012)
"Drawing on the most powerful and compelling research data to date and connecting this research to linguistic human rights, this book explores the conditions and practices of robust bilingual and multilingual educational innovations in both system-wide and minority-settings and what it is that makes these viable. It demonstrates how, in poor countries where educational practices are inclusive of linguistic diversity and responsive to local conditions and community participation, implementation of bilingual education even within limited budgetary investment can be successful"--
Includes bibliographical references and index.
ENH
Book Finder International
Keywords: Education, Bilingual -- Cross-cultural studies; Multilingualism -- Cross-cultural studies; Multicultural education -- Cross-cultural studies; EDUCATION / Bilingual Education; EDUCATION / Comparative; FOREIGN LANGUAGE STUDY / English as a Second Language